Emerging trends of nosocomial Citrobacter species surgical wound infection: concern for infection control - B Thapa; D Karn; K Mahat (Nepal Journal of Dermatology, Venereology & Leprology)
Background Surgical wound infection is a common problem among patients who undergo operation. Several factors play important role in this infection process including endemic nosocomial infection without proper infection control measures.